Kontektualisasi Hukum Menikahi Pezina Pada Fenomena Married by Accident Perspektif Hadis - Nasrulloh Nasrulloh; Farhanah Az Zahrowani Nabila; Titi Rusydiyati Al Kaswy (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Legal Contextualization of Marrying Adulterers in the Married by Accident Phenomenon from Hadith PerspectiveThis article contains the legal contextualization of marrying adulterers on the emergence of the phenomenon of Married by Accident in Indonesia with the hadith in Sunan Abu Dawud number 2052. The discussion regarding the quality of the hadith in Sunan Abu Dawud number 2052 in its use as evidence (hujjah) and how the correlation between the meaning of the hadith and the contextualization of the rules of marrying an adulterer in the phenomenon of married by accident is interesting to be discussed by seeing the position of hadith as a muttafaq source in addressing all of the problems in human life. The method used in this study was normative qualitative with the critic sanad and matan hadis approach, in which all of those were analized using texual, intertextual and contextual interpretation theories. The results obtained show that the quality of the hadith prohibiting adulterous marriage on Sunan Abu Dawud number 2052 can be categorized as authentic hadith and can be used as evidence (hujjah) in the legal decision (istinbath) of marriying adulterers. Meanwhile, the results of the analysis of the meaning of the hadith narrated by Abi Dawud stated that if it is correlated with the current Married by Accident phenomenon, the law of marrying an adulterer was permitted by looking at the benefits in it